Harmonizacja rachunkowości a standardy edukacji - Kwiecień, Mirosława (Harmonization of Accounting Versus Standards of Education, 2005)
The article contains theses to discussion about education and harmonization of accounting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 98-101